SOCIAL REALITY CONSTRUCTION IN THE TECHNO-SOCIAL WORLD: NEW ASPECTS OF SOCIOLOGICAL CONCEPTUALISATION - Osipov, Gennady; Pinchuk, Antonina; Karepova, Svetlana Karepova; Nekrasov , Sergey; Tikhomirov, Dmitry (Revista Inclusiones, 2021)
The paper considers the conceptual approaches to social reality construction amidst the development of digital technology forming the techno-social space, in which socio-cultural and technological aspects of human life and society are intertwined in the context of mutually conditioned changes. Based on the concepts of phenomenology, the mental bases of the social world exploration are enunciated and the role of digital technology in the social distribution of knowledge through new forms of everyday practices of communication is analyzed. Building upon the conceptual ideas of materialist phenomenology, it states that one needs to take into consideration the physical infrastructure of social communications in the current situation, because there is a duplicitous nature of worldviews and reality through material and social aspects. The thesaurus approach places a special emphasis on a certain set of everyday knowledge being internalized in the primary and secondary socialization that allows the individual to navigate in the environment. Based on the concepts of this approach, features of the thesaurus worldviews formed in the context of virtual and augmented reality are considered. Features of knowledge production and ways of its acquiring through the application of new analytical methods for big data processing are separately analyzed. It is shown that the intensified use of information technologies in the intellectual activity of a modern individual deepens the functional relationship between them in the acquiring of new knowledge. It can be reflected in the thesaurus structure. It is concluded that digital technology does not simply mediate the real-world exploration, acting as a neutral guide but transforms the construction of social reality.